Financial risk assessment of biomass power plant: a case study of Sungnoen Rice Husk Power Plant in Nakornratchasima - Klairung Kositthanasarn; Marpaung, Charles O.P.; Weerakorn Ongsakul; Singh, Jai Govind; PEA; Asian Institute of Technology Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
This research presents the risk analysis approach for the financial evaluation of biomass power plant a case study of Sungnoen rice husk power plant in Nakornratchasima. The risk analysis is applied by using Monti Carlo Simulation (MSC) approach which uses random variables with a specific probability distribution. The program called 3@risk3 has been used in the study. This study analyzed seven cases representing different combination of the uncertainty factors, namely: plant factor, fuel cost (rice husk), maintenance cost and discount rate. Both certain and uncertain factors are involved in the evaluation of biomass power plant projects. Each case results the net present value (NPV) probability function. The results of the risk analysis in term of the NPV are compared with the base case. Each case reveals the different effect on the NPV. Plant factor which is internal factor has highest effect on the project NPV. In contrast, Discount rate that is external factor has lowest affect. PEI who is continue the project could aware both internal and external factor, these risk affect and unexpected results which are shown by this study. The probability of the NPV is important to make decision that the project attractive or not. NPV of the studied rice husk power plant project would have negative value during the first six year of the project, which implies that the return on investment cannot be made under this period. From year of 7th onwards, NPV of the studied rice husk power plant project would have positive value rendering return on investment. Moreover, it is crucial for project developer to formulate an emergency plan when there is unexpected situation. Therefore, this project is always attractive
A research submitted in partial fulfillment of the requirements for the degree of Master of Science in Energy
Thesis (M.Sc.) - Asian Institute of Technology, 2011
Keywords: Biomass energy -- Risk assessment -- Thailand -- Nakonratchasima